(untitled) (Eurasian Journal of Ecology, 2016)
Age changes of erythrocyte membranes’ resistance and biochemical parameters of blood of rats were researched. It is shown, that the young organism is most sensitive to the oxidative stress leading to the damaging of integrity of cell membranes whereas erythrocyte membranes of adult animals differed high stability. At ageing take place the decreasing of resistency of erythrocyte membranes and changing of biochemical parameters of blood.